Longitudinal gut microbial signals are associated with weight loss: insights from a digital therapeutics program - Kumbhare, Shreyas V.; Pedroso, Inti; Joshi, Bharat; Muthukumar, Karthik M.; Saravanan, Santosh K.; Irudayanathan, Carmel; Kochhar, Gursimran S.; Dulai, Parambir S.; Sinha, Ranjan; Almonacid, Daniel E. (Frontiers in Nutrition, 2024)
The gut microbiome's influence on weight management has gained significant interest for its potential to support better obesity therapeutics. Patient stratification leading to personalized nutritional intervention have shown benefits over one-size-fit-all diets. However, the efficacy and impact on the gut's microbiome of personalizing weight loss diets based on individual factors remains under-investigated. This study assessed the impact of Digbi Health's personalized dietary and lifestyle program on weight loss and the gut microbiome end-points in 103 individuals. Participants' weight loss patterns and gut microbiome profiles were analyzed from baseline to follow-up samples. Specific microbial genera, functional pathways, and communities associated with BMI changes and the program's effectiveness were identified. 80% of participants achieved weight loss. Analysis of the gut microbiome identified genera and functional pathways associated with a reduction in BMI, including Akkermansia, Christensenella, Oscillospiraceae, Alistipes, and Sutterella, short-chain fatty acid production and degradation of simple sugars like arabinose, sucrose, and melibiose. Network analysis identified a microbiome community associated with BMI, which includes multiple taxa known for associations with BMI and obesity. The personalized dietary and lifestyle program positively impacted the gut microbiome and demonstrated significant associations between gut microbial changes and weight loss. These findings support the use of the gut microbiome as an endpoint in weight loss interventions, highlighting potential microbiome biomarkers for further research.